Floral Design of the Liv Oval Brooches of the 12th–13th Centuries in the Context of the Medieval Christian Art - Spirģis, Roberts (Actual Problems of Theory and History of Art, 2021)
Paired oval brooches were typical for the culture of ancient Livs. They were used to fasten female dress on the shoulders. The first brooches were made in the Lower Daugava at the turn of the 10th and 11th centuries. Before that the Livs had worn imported adornments in the Scandinavian Beast Style. The appearance of the brooches with floral design in the middle of the 12th century caused a new turn in the jewelry art of Livs.The floral design originated from the East. It was associated with the symbol of the garden of Eden. This idea was also adopted by Christian art. The interminable interweaving of the tree of life, flowers, laurel leaves and bunches of grapes symbolized the arrangement of the Kingdom of God, or the Paradise where the souls of righteous Christians would go after death.Article will consider not only the separate details, the so-called brooches with palmettes, it is intended to expose Christian themes in the local adornments (cross and virtues of Jesus) as well as to show the introduction of the new religious symbols in of the earlier Scandinavian decoration (the images of the four Evangelists, cross, heaven, and plots of Christian bestiary).The prototypes were identified among the Byzantine imperial regalia and in the iconography of the Theotokos. They help to shed light on the possible context of the appearance of the oval brooches in the Northern Europe and explain the duration of use of these adornments among Livs.
Keywords: Livs; oval brooches; floral design; Christianization; symbolism